Evidence of a significant role of glutathione reductase in the sulfur assimilation pathway. (11th January 2020) - Cohen, Anner; Hacham, Yael; Welfe, Yochai; Khatib, Soliman; Avice, Jean‐Christophe; Amir, Rachel
Summary: With the objective of studying the role of glutathione reductase (GR) in the accumulation of cysteine and methionine, we generated transgenic tobacco and Arabidopsis lines overexpressing the cytosolic At GR1 and the plastidic AtGR2 genes. The transgenic plants had higher contents of cysteine and glutathione. To understand why cysteine levels increased in these plants, we also used gr1 and gr2 mutants. The results showed that the transgenic plants have higher levels of sulfite, cysteine, glutathione and methionine, which are downstream to adenosine 5′ phosphosulfate reductase (APR) activity. However, the mutants had lower levels of these metabolites, while the sulfate content increased. A feeding experiment using 34 SO4 2– also showed that the levels of APR downstream metabolites increased in the transgenic lines and decreased in gr1 compared with their controls. These findings, and the results obtained from the expression levels of several genes related to the sulfur pathway, suggest that GR plays an essential role in the sulfur assimilation pathway by supporting the activity of APR, the key enzyme in this pathway. GR recycles the oxidized form of glutathione (GSSG) back to reduce glutathione (GSH), which serves as an electron donor for APR activity. The phenotypes of the transgenic plants and the mutants are not significantly altered under non‐stress and oxidative stress conditions. However, when germinating on sulfur‐deficient medium, the transgenic plants grew better, while the mutants were more sensitive than the control plants. The results give substantial evidence of the yet unreported function of GR in the sulfur assimilation pathway. Significance Statement: This study showed that differences in the expression levels of glutathione reductase (GR) in tobacco and Arabidopsis transgenic and mutant plants significantly affect the level of metabolites associated and in the sulfur assimilation pathway. The findings suggest that GR plays an important role in the activity of 5′ phosphosulfate reductase, a key enzyme of the sulfur assimilation pathway and cysteine formation, and thus give substantial evidence of the function of GR in plants.